PENGARUH PENYIMPANAN ARSIP BLOK PARAFIN TERHADAP KUALITAS PREPARAT JARINGAN - Nurdianti, Dinda; Wiryanti, Wiwin; Durachim, Adang; Gustira Rahayu, Ira (Jurnal Kesehatan Siliwangi, 2024)
Paraffin block archive storage is the process of maintaining and managing used paraffin blocks. "A standardized paraffin block archive storage system will facilitate access for diagnostic purposes and help maintain the quality of the paraffin blocks over the long term. If the storage system is not standardized, it can cause several problems, such as delaying diagnostic services and reducing the quality of tissue preparations. Most paraffin blocks can be stored at temperatures of 20-27°C. Paraffin blocks should not be exposed to temperatures exceeding 27°C, as improper storage can cause the paraffin to soften and damage the tissue, reducing the quality of tissue preparations. This study aims to determine the effect of paraffin block archive storage on tissue preparation quality. The research samples used paraffin block archives stored in cabinets for 5 and 6 years, and paraffin block archives stored in plastic for 5 and 6 years. The quality of tissue preparations was assessed based on the clarity of the arrangement of bile duct cell walls, namely mucosa, lamina propria, muscularis and serosa microscopically and the color contrast of nuclei and cytoplasm using ImageJ software. The results of the study showed that there was no significant effect of paraffin block archive storage on tissue preparation quality. Further research needs to be conducted on the storage duration of paraffin block archives in wooden and plastic cabinets over a period of 10 years, as well as obtaining information related to the initial condition of the paraffin blocks, including color, texture, shape,and tissue authenticity.